Development of free neuromasts in larvae of mouse grouper, Cromileptes altivelis - Daning Tuzan, Audrey; Mukai, Yukinori; Senoo, Shigeharu (INOC-UMS, 2006)
This study was conducted to clarify the development of free neuromasts in larvae of mouse grouper Cromileptes altivelis. A pair of free neuromasts was observed behind the eyes in newly hatched larvae. The number of free neuromasts increased with larval growth. Three-day-old larvae started ingesting rotifers and had 6 pairs of free neuromasts on the head and 4 free neuromasts on the unilateral side of the trunk. Free neuromasts were distributed around the eyes on the head, and on the middle of the trunk. The apical surface of the free neuromasts changed in outline from a circular shape to a lozenge shape, suggesting that the shape of the cupula changes from a stick-like shape to a vane-like shape. The number of sensory cells of the free neuromasts increased with larval growth. The orientation of physiological maximum sensitivity of free neuromasts, decided from the polarity of the sensory cells, coincided with the minor axis of the lozenge-shaped outline of the apical surface. The polarity of the trunk neuromasts was usually oriented along the antero-posterior axis of the fish body, but a few had dorso-ventral orientation. On the head, the free neuromasts were oriented on lines tangential to concentric circles around the eye, hence the free neuromasts on the head could detect stimuli from various angles. It was considered that free neuromasts of mouse grouper play an important role in avoiding predators, especially until the eyes begin to function.